Teorie e sperimentalismo progettuale per la ricerca in tecnologia dell'architettura / Theories and experimental design for research in architectural technology - Rossi, Monica; Ottone, Federica (Scuole di dottorato, 2013)
The volume, which gathers reflections on the theme of the city intended as a field of experimentation, provides an updated overview on doctoral (PhD) and post-doctoral research in Architectural Technology, and offers wide-ranging theoretical insights as well as a broad range of specialized applications. The environmental approach, which welcomes suggestions from the surrounding areas, enhancing their "material culture", shows the common trait on which many of the research topics presented here are based.